Super magic deficiency of graphs. (18th August 2022) - Raheem, A.; Javaid, M.; Hanif, M.; Hasni, R.; Shah, Nasir
Abstract: An edge-magic total (EMT) labeling for graph Γ is one-one map from π : V (Γ) ∪ E (Γ) → 1, 2, … , | V (Γ)|+| E (Γ)|, so that there manage a number c along a rule that for every edge, uv ∈ E (Γ), π ( u ) + π ( uv ) + π ( v ) = c . And if all vertices are assigned with positive integral numbers 1, 2, … , | V (Γ)| then this type of labeling is called a super EMT labeling. Super edge-magic, deficiency for graph Γ, represented as μs (Γ), which is least positive integral number n so that Γ∪ nK 1 has super EMT labeling, or ∞, if there does not exist n . In present article, compute a super edge-magic deficiency for the graph .